1957
DOI: 10.1017/s0025315400017021
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution and significance of organically bound iodine in the ascidianCiona intestinalisLinnaeus

Abstract: Some features of the organization of the endostyle of Ciona intestinalis are described. Autoradiographs show that bound iodine is present in a limited area of the epithelium (zone 7), where it is associated with characteristic secretory inclusions which are found only in this zone. These are regarded as providing the molecular basis for the iodination process, and are termed 'thyroidal granules', since they resemble in certain properties the similarly named granules of the endostyle of the ammocoete; it is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

1958
1958
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 11 publications
0
36
0
1
Order By: Relevance
“…The morphogenesis of this gland, that originates from the embryonic pharyngeal epithelium, supports the homology. In addition, endostyle incorporates iodine (Barrington, 1957(Barrington, , 1958Salvatore, 1969), and the expression of homolog thyroidspecific developmental genes during endostyle development has been reported (McCauley and Bronner-Fraser, 2002; Ogasawara, 2000; Ogasawara and Satoh, 1998; Ogasawara et al, 2001; Venkatesh et al, 1999). The zones 7, 8 and 9 of the C. intestinalis endostyle have been retained the endostyle regions homologs to the vertebrate thyroid (Ogasawara and Satoh, 1998), disclose peroxidase activity (Fujita and Sawano, 1979;Kobayashi et al, 1983), and a specific TPO has been identified in the zone 7 (Ogosawara et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The morphogenesis of this gland, that originates from the embryonic pharyngeal epithelium, supports the homology. In addition, endostyle incorporates iodine (Barrington, 1957(Barrington, , 1958Salvatore, 1969), and the expression of homolog thyroidspecific developmental genes during endostyle development has been reported (McCauley and Bronner-Fraser, 2002; Ogasawara, 2000; Ogasawara and Satoh, 1998; Ogasawara et al, 2001; Venkatesh et al, 1999). The zones 7, 8 and 9 of the C. intestinalis endostyle have been retained the endostyle regions homologs to the vertebrate thyroid (Ogasawara and Satoh, 1998), disclose peroxidase activity (Fujita and Sawano, 1979;Kobayashi et al, 1983), and a specific TPO has been identified in the zone 7 (Ogosawara et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Such are also to be found in the food cord in the dorsal groove, into which, as is well known, material secreted by the endostyle and gill bars is swept in consequence of the action of the pharyngeal ciliation, while the food cords in the mid-gut and intestine also give strong images. It is always to be remembered that food organisms themselves may bind iodine and contribute to such images (Barrington, 1957), but it seems wholly improbable that this could account for all of the latter; I agree, therefore, with Thomas (1956), who noted similar images in his own preparations, that the iodinated secretion of the endostyle is ultimately incorporated into the food cords.…”
Section: Autoradiographsmentioning
confidence: 64%
“…At the base of the endostylar groove is a group of cells, here termed' zone 1" which closely resemble the correspondingly placed zone 1 cells of Ciona (Barrington, 1957). They possess slender and densely staining nuclei, long cilia, and a conspicuously striated cell border.…”
Section: Endostyle Ii9mentioning
confidence: 99%
“…This homology, originally based on the reorganization of the larval endostyle into the adult thyroid in lampreys (Muller, 1873), is supported by iodine binding, peroxidase activity, thyroglobulin, and calcitonin-like cells both in endostyles and in thyroids (Gorbman and Creaser, 1943;Barrington, 1957;Thorpe et al, 1972;Thorndyke, 1978;Thorndyke and Probert, 1979;Kobayashi et al, 1983;Fredriksson et al, 1985Fredriksson et al, , 1988.…”
Section: Introductionmentioning
confidence: 99%